Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3945/ajcn.116.142075
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled clinical trial of choline supplementation in school-aged children with fetal alcohol spectrum disorders

Abstract: Background: Prenatal alcohol exposure results in a broad range of cognitive and behavioral impairments. Because of the long-lasting problems that are associated with fetal alcohol spectrum disorders (FASDs), the development of effective treatment programs is critical. Preclinical animal studies have shown that choline, which is an essential nutrient, can attenuate the severity of alcohol-related cognitive impairments. Objective: We aimed to translate preclinical findings to a clinical population to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 59 publications
0
52
1
1
Order By: Relevance
“…There were adequate data from all studies for quantitative comparison of the control and intervention groups for each outcome. However, there were no nonexposed control subjects included in the studies by Nguyen and colleagues () or Wozniak and colleagues () and so the effect of alcohol alone on the measured outcomes could not be evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were adequate data from all studies for quantitative comparison of the control and intervention groups for each outcome. However, there were no nonexposed control subjects included in the studies by Nguyen and colleagues () or Wozniak and colleagues () and so the effect of alcohol alone on the measured outcomes could not be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…For Nguyen and colleagues (), heavy prenatal alcohol exposure was determined via retrospective review of medical, social services, or adoption records and was defined as ≥4 drinks/occasion ≥1 time/wk or ≥14 drinks/wk during pregnancy. In the study reported by Wozniak and colleagues (), FASD was diagnosed using the modified Institute of Medicine (IOM) criteria (Hoyme et al., ) and the Centers for Disease Control and Prevention (CDC) criteria for FASD (Bertrand et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional supplementation has been found to attenuate FASD symptomology in some animal models [98]. Results in human studies are limited and inconsistent [113][114][115].…”
Section: Prenatal Nutritionmentioning
confidence: 99%